Marginalised Muslim women in Kerala, India: the interplay between empowerment and social exclusion - Shanuga Cherayi and C.Satheesh Kumar (Research on Humanities and Social Sciences, 2014)
We examined how empowerment of Muslim women influences social exclusion. A total of 101 Muslim women from rural areas, under below poverty line, were selected using probability sampling. We measured empowerment and social exclusion using standardized measures and data were analysed at univariate, bivariate and multivariate levels. Analysis reveals that overall scores on empowerment was moderate and high level of social exclusion. Empowerment subscales viz., domestic consultation (β=.194) and political empowerment (β=.199) have significantly contributed to social exclusion. It reveals that how empowerment alongside with socio-demographic variables such as duration of marriage (β=.534), age (β=-.407) and education (β=.371) influenced social exclusion. The study concludes that less empowerment significantly accelerate social exclusion. Implications of the results are discussed